The Need For Achievement, Risk-Taking Propensity, And Entrepreneurial Intention Of The Generation Z - Tri Siwi Agustina; Dea Sawitri Fauzia (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Entrepreneurial intention is affected by various factors, namely the need for achievement and risk-taking propensity. This study aims to fill a research gap regarding numerous previous studies about Student Entrepreneurship Program (PMW). However, there has not been a study that involved the need for achievement and risk-taking propensity by mediating entrepreneurial attitudes as a form entrepreneurial intention among the Generation Z of PMW participants. The research approach is quantitative by distributing questionnaires to 61 Generation Z who were the participants of PMW 2020. Hypothesis tests were carried out by the Path Analysis. The results of this study indicated that: the need for achievement and the risk-taking propensity was proven to positively influence entrepreneurial intentions; however, the entrepreneurial attitude was not proven to mediate the influence of the need for achievement on entrepreneurial intentions; as well as the entrepreneurial attitude was not proven to mediate the influence of the need for achievement on entrepreneurial intentions.